2016
DOI: 10.14348/molcells.2016.0033
|View full text |Cite
|
Sign up to set email alerts
|

BK Knockout by TALEN-Mediated Gene Targeting in Osteoblasts: KCNMA1 Determines the Proliferation and Differentiation of Osteoblasts

Abstract: Large conductance calcium-activated potassium (BK) channels participate in many important physiological functions in excitable tissues such as neurons, cardiac and smooth muscles, whereas the knowledge of BK channels in bone tissues and osteoblasts remains elusive. To investigate the role of BK channels in osteoblasts, we used transcription activator-like effector nuclease (TALEN) to establish a BK knockout cell line on rat ROS17/2.8 osteoblast, and detected the proliferation and mineralization of the BK-knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Stable suppression of BKs in hMSCs with shRNA significantly decreased both mRNA and protein levels of PPARγ and osteocalcin (intermediate and early biomarkers of adipogenesis and osteogenesis, respectively) (Figure ) (Zhang et al, ). A recent study also showed that BK channel knockout in MSC‐derived osteoblasts largely reduced osteocalcin, osteopontin and Runx2 expression (Hei et al, ). Similarly, K Ca channels have been found to be involved in the initiation of other SCs.…”
Section: Kca's In Mesenchymal Stem Cells and The Differentiation Processmentioning
confidence: 95%
“…Stable suppression of BKs in hMSCs with shRNA significantly decreased both mRNA and protein levels of PPARγ and osteocalcin (intermediate and early biomarkers of adipogenesis and osteogenesis, respectively) (Figure ) (Zhang et al, ). A recent study also showed that BK channel knockout in MSC‐derived osteoblasts largely reduced osteocalcin, osteopontin and Runx2 expression (Hei et al, ). Similarly, K Ca channels have been found to be involved in the initiation of other SCs.…”
Section: Kca's In Mesenchymal Stem Cells and The Differentiation Processmentioning
confidence: 95%
“…Immunocytochemistry analysis was performed according to a previous report 21 . The cells were seeded onto slides.…”
Section: Methodsmentioning
confidence: 99%
“…Total proteins from the long bones or cells were analyzed by western blotting using a modified method 21 . Briefly, the bone powder and cells were lysed with RIPA buffer supplemented with 1% protease inhibitor cocktail (P0013B; Beyotime) for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations